1996
DOI: 10.1023/a:1016047215907
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A clear charge effect on complexation, attraction in the case of cationic drugs and perhaps inhibition in the case of anionic drugs, was seen with the SBE7-beta-CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…This result indicated the very high affinity between NAP and SBE-ßCyd and showed that its negative charge did not inhibit complexation of the acidic drug in unbuffered aqueous solution (pH ≈5), in spite of the presence of about 60% of the dissociated anionic form, as determined from its pK a value [9]. To explain the better performance of SBE-ßCyd with respect to the native carrier, it has been hypothesized, that, as in the case of the methyl-ß-derivative, the presence of substituents can extend the hydrophobic region of the Cyd cavity, thus favouring and stabilizing inclusion complexation of the hydrophobic guest molecule [3].…”
Section: Interaction In Aqueous Solutionmentioning
confidence: 83%
See 1 more Smart Citation
“…This result indicated the very high affinity between NAP and SBE-ßCyd and showed that its negative charge did not inhibit complexation of the acidic drug in unbuffered aqueous solution (pH ≈5), in spite of the presence of about 60% of the dissociated anionic form, as determined from its pK a value [9]. To explain the better performance of SBE-ßCyd with respect to the native carrier, it has been hypothesized, that, as in the case of the methyl-ß-derivative, the presence of substituents can extend the hydrophobic region of the Cyd cavity, thus favouring and stabilizing inclusion complexation of the hydrophobic guest molecule [3].…”
Section: Interaction In Aqueous Solutionmentioning
confidence: 83%
“…In the present work, we thought it worthy of interest to extend the study to some recently available ionic cyclodextrins, with the objective of evaluating the possible role of the cyclodextrin charge in the interaction with an acidic drug such as naproxen (pK a 4.8 [9]). Sulfobutylether-ß-cyclodextrin 0731 and trimethylammonium-ß-cyclodextrin were selected as, respectively, anionically and cationically charged carriers and their performance towards naproxen was compared with that of the parent ß-cyclodextrin and of the methyl-ß-cyclodextrin (the best drug partner among the previously examined neutral ß-derivatives [7]).…”
Section: Introductionmentioning
confidence: 99%
“…46) On the other hand, SBE7-b-CyD was found to serve as both a solubility modulating and an osmotic pumping agent for the controlled-porosity osmotic pump tablets, from which the release rate of both highly and poorly water-soluble drugs can be controlled precisely. [144][145][146][147] The ordinary delayed release profile can be obtained by the use of enteric type CME-b-CyD. 148) As shown in Fig.…”
Section: )mentioning
confidence: 99%
“…One example is a study by Rajewski et al [18,19] who investigated the role of charge by comparing the binding of neutral and charged cyclodextrins with neutral and charged guests. They found that the negatively charged sulfobutyl ether b-CD had a higher binding affinity than neutral b-CD for neutral guest species.…”
Section: Introductionmentioning
confidence: 99%